2021
DOI: 10.31234/osf.io/nfwru
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Open Gallery for Arts Research (OGAR): An Open-Source Tool for Studying the Psychology of Virtual Art Museum Visits

Abstract: To expand the tools available to arts researchers in psychology, we present the Open Gallery for Arts Research (OGAR), a free, open-source tool for studying visitor behavior within an online gallery environment. OGAR is highly extensible, allowing researchers to modify the environment to test different hypotheses, and it affords assessing a wide range of outcome variables. After describing the tool and its development, we present a proof-of-concept study that evaluates OGAR’s usability and performance and illu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…OGAR collects and allows the designer to access a robust set of time-stamped variables about the user, such as their movement and gaze, and it has been evaluated as an acceptable alternative to in-person research in terms of navigation and artwork viewing behavior. In a proof-of-concept study using a small sample of 44 adults, Rodriguez-Boerwinkle et al (2022) demonstrated some basic indicators of OGAR's validity: as the gallery size increased, visitors spent longer in the gallery and traveled further within it. The participants actively approached and viewed the available artworks, and they were able to successfully navigate the space without major usability concerns.…”
Section: Virtual Galleries As a Tool For Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…OGAR collects and allows the designer to access a robust set of time-stamped variables about the user, such as their movement and gaze, and it has been evaluated as an acceptable alternative to in-person research in terms of navigation and artwork viewing behavior. In a proof-of-concept study using a small sample of 44 adults, Rodriguez-Boerwinkle et al (2022) demonstrated some basic indicators of OGAR's validity: as the gallery size increased, visitors spent longer in the gallery and traveled further within it. The participants actively approached and viewed the available artworks, and they were able to successfully navigate the space without major usability concerns.…”
Section: Virtual Galleries As a Tool For Researchmentioning
confidence: 99%
“…For this reason, the current study will use the Open Gallery for Arts Research (OGAR; Rodriguez-Boerwinkle et al, 2022), an online virtual gallery tool for studying the psychology of the virtual art museum visit. The opensource gallery software allows researchers to design a non-immersive 3D environment and embed it in a webpage or online survey software where it can then be accessed by participants recruited through online survey pools or by lab-based PERSONALITY & VIRTUAL ART VIEWING 8 participants with lab hardware.…”
Section: Virtual Galleries As a Tool For Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Such studies have aimed to provide researchers or museum experts details about the relationship between visitors’ behavior when viewing exhibitions and artworks and their satisfaction [ 18 ]. For example, Lanir et al [ 19 ] proposed a system that provides museum experts with visualized visitor behavior information, and Rodriguez-Boerwinkle, Boerwinkle, and Silvia [ 20 ] developed the method for art research by tracking visitors in a virtual museum environment. Even though visitor behavior and reaction data have been collected, these collected data have been used as information sources for researchers or museum operators only and have not been provided to museum visitors.…”
Section: Introductionmentioning
confidence: 99%